If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6h + 13 = 5 Reorder the terms: 13 + 6h = 5 Solving 13 + 6h = 5 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 6h = 5 + -13 Combine like terms: 13 + -13 = 0 0 + 6h = 5 + -13 6h = 5 + -13 Combine like terms: 5 + -13 = -8 6h = -8 Divide each side by '6'. h = -1.333333333 Simplifying h = -1.333333333
| m+123+29=180 | | -3-(-56)= | | -d^2+d=-6 | | f=3(22) | | -2+2.3w=10 | | 4(a+3)=6a+12 | | m+123+23=180 | | 12x+11+-4= | | 266=-7(-7x+11) | | x+15=7x-9 | | 4n=944 | | 4=x/13+1 | | 7x+3y=37 | | 4a+3=6a+12 | | 23=-1+6(3x-2) | | 7n-4n+11n= | | 4x+21=5x+10 | | 8(3)=v | | 11c+21=-24 | | 4(cos^2)x+7(sinx)-7=0 | | -8(4+4n)=-288 | | 4(cos^2)x+7sinx-7=0 | | -39+7k=2(7k+3)+2k | | 53=-2-(1-7n) | | 3*x+3=30 | | 50y+25x= | | y=-2x+22 | | 29t=319 | | 17+x=18*x | | 2(x+8)+7=43 | | x^3-12x^2+35= | | -6=-(p-1) |